Exploring butterfly diversity in urban landscapes: A case study from Depok, Indonesia - Reza Dino Mahardika; Nafidza Nur Shabrina; Syafiq Alan Setyawan; Mohamad Isnin Noer (Bioma, 2025)
Depok City is one of Jakarta's satellite cities with a high level of urbanisation that is reducing the living space for butterflies. Green open spaces (GOS) play an important ecological role and have the potential to become habitats for a diverse range of butterfly species in urban areas. The existence of GOS has the potential to provide food plants and environmental preferences that support the living space of butterflies. Research needs to be conducted to determine the potential of these GOS as habitats for butterfly diversity in urban areas. This study aims to determine the diversity, abundance, density, and evenness of butterfly species in Depok City's GOS. The study was conducted in five GOS in Depok City using the Visual Encounter Survey (VES) sampling technique. We found Depok’s GOS showed moderate butterfly diversity and species evenness indices with an average density of 10.04 individuals/ha. GOS’s temperature and humidity does not determine the population variables; while light intensity and area sizes significantly related to abundance, Shannon-Wiener’s H’ and density of butterflies. Pielou’s E is not determined by any abiotic variables. Depok’s green spaces show strong promise as refugia supporting butterfly diversity in urban ecosystems.